Mandibular reconstruction with microvascularized graft after ameloblastoma resection: case series (Research, Society and Development, 2021)
Ameloblastoma is a locally aggressive and highly infiltrative tumor with a high recurrence rate. Its multicystic form the recommended treatment is resection with a safety margin, which results in significant facial defects with esthetic and functionals repercussions. Microvascular surgery revolutionized the reconstruction of significant defects because these grafting techniques allow a more satisfactory aesthetic and functional restoration. This study aimed to report a series of cases of reconstructions of mandibular defects using microvascularized fibular graft after ameloblastoma resection. Six patients were included in this study, and we collected data related to the surgical procedure, diagnosis, complications and follow-up. The patients were characterized as four women and two men, with a mean age of 23.8 years, with a diagnosis of mandibular ameloblastoma located mainly in the body, angle and mandibular ramus. These patients underwent lesion resection, resulting in defects larger than 5 cm, which justified using a microvascularized fibular graft for its reconstruction. The patients evolved well, with good results and without recurrences or complications in a postoperative follow-up of 2 to 5 years. Ameloblastoma is a lesion that reaches large dimensions and causes excellent cosmetic and functional damage. The microvascularized graft is an alternative in reconstructing significant defects and allows satisfactory morphofunctional reestablishment with minimal complications.